Specification for hydraulic fluid power. Four-screw split-flange connections for use at pressures of 2, 5 MPa to 40 MPa (25 bar to 400 bar). Type 1 metric series and type 11 inch series. (15th March 1995) - British Standards Institution,
No abstract available